2017
DOI: 10.1002/ajhb.22979
|View full text |Cite
|
Sign up to set email alerts
|

Segmented sleep in a nonelectric, small‐scale agricultural society in Madagascar

Abstract: Sleep in this population is segmented, similar to the "first" sleep and "second" sleep reported in the historical record. Moreover, although average sleep duration and quality were lower than documented in Western populations, circadian rhythms were more stable across days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 51 publications
6
70
0
Order By: Relevance
“…Furthermore, there was no effect on wake time or total sleep duration, despite impacts on circadian timing. Similarly, in a rural community in Madagascar, the use of electric field lanterns for one week had no effect on participants' sleep (Samson et al, 2017b). In another study, researchers took eight participants camping without electric lights (Wright et al, 2013).…”
Section: Human Sleep: Real-world Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there was no effect on wake time or total sleep duration, despite impacts on circadian timing. Similarly, in a rural community in Madagascar, the use of electric field lanterns for one week had no effect on participants' sleep (Samson et al, 2017b). In another study, researchers took eight participants camping without electric lights (Wright et al, 2013).…”
Section: Human Sleep: Real-world Comparisonsmentioning
confidence: 99%
“…Accordingly, a laboratory study found that people adopted biphasic sleep when exposed to 14 hr of darkness each night (Wehr, 1992). There is also evidence of biphasic sleep in some contemporary communities without electricity (Samson et al, 2017b), but not others (Beale et al, 2017;de la Iglesia et al, 2015;Peixoto, da Silva, Carskadon, & Louzada, 2009;Samson, Crittenden, Mabulla, Mabulla, & Nunn, 2017a;Yetish et al, 2015). Despite some dispute about the likely origins of biphasic sleep in humans (Ekirch, 2016;Yetish et al, 2015), sleep in western societies has clearly changed in recent history (Ekirch, 2015).…”
Section: Human Sleep: Real-world Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study found the average sleep times in three different hunter-gatherer groups range from 5.7 to 7.1 h, with an overall average of 6.5 h [27]. Another set of authors observed a nearly identical average sleep time for agriculturalists in rural Madagascar [28], while a study of a Haitian population lacking access to electricity identified the sleep duration as 7 h [29]. …”
Section: Humans Sleep Less Than Other Primatesmentioning
confidence: 99%
“…In addition, napping is less common than expected in hunter-gatherers [27], yet perhaps more common and longer in agriculturalists, potentially adding up to an hour of sleep per day [28]. Taken together, 7 h is a good upper-level estimate of typical human sleep, with many ancestral populations likely sleeping less than this when ecological or social conditions constrain options for safe sleep.…”
Section: Humans Sleep Less Than Other Primatesmentioning
confidence: 99%